Conservation behavior among government staff in Perlis / Muhammad Faishal Ishak - Ishak, Muhammad Faishal (2014)
This research paper title is “Conservation behavior among government staff in Perlis. The researcher intended to identify the several factor factors that influence the respondents towards conservation behavior’. Therefore the researcher has proposed four independent variables that might influence the respondents intention namely Personal attitude, subjective norm, Perceived behavioral control and understanding of conservation behavior. Further detailed of the variables is discussed in Chapter 2. On Chapter 1 of the report, the researcher includes information regarding the background of the study, the objective of the study and etc. The population for this research in the area in Perlis and the researcher decided to take 150 of the government staff that work in Perlis as the research sample, further detailed on the research methodology was discuss in Chapter 3. In order to achieve the research objective, the researcher had conduct five analysis which are frequency analysis, descriptive analysis, reliability analysis, hypothesis testing (correlation analysis) and multiple regression. The entire analysis finding is present in Chapter 4. The last chapter which is Chapter 5 discuss regarding conclusion and recommendations from the researcher.